2010
DOI: 10.1007/s11738-010-0520-z
|View full text |Cite|
|
Sign up to set email alerts
|

Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China

Abstract: The karst habitats of southwestern China are characterized by a highly heterogeneous distribution of water resources. We hypothesized that the clonal integration between connected ramets of the clonal vine Ficus tikoua was an important adaptive strategy to the patchy distribution of water resources in these habitats. We grew ramet pairs (each consisting of a parent and an offspring ramet) in both homogeneously and heterogeneously watered conditions. The offspring ramets were wellwatered, whereas their connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Thus another possible explanation is that the loss of apical dominance caused by stolon severance promotes the growth of supporting ramets. Significant costs of water export in clonal plants also have previously been reported in C. flacca and Ficus tikoua spanning a gradient in water availability [39], [43]. However, this contrasts with the results in H. bonariensis [37], C. hirta [39], P. anserina [80] and Buchloe dactyloides [88], which showed that clonal integration confers benefits on drought stressed ramets but no costs on the connected supporting ramets.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus another possible explanation is that the loss of apical dominance caused by stolon severance promotes the growth of supporting ramets. Significant costs of water export in clonal plants also have previously been reported in C. flacca and Ficus tikoua spanning a gradient in water availability [39], [43]. However, this contrasts with the results in H. bonariensis [37], C. hirta [39], P. anserina [80] and Buchloe dactyloides [88], which showed that clonal integration confers benefits on drought stressed ramets but no costs on the connected supporting ramets.…”
Section: Discussionmentioning
confidence: 64%
“…In clonal plants, physiological integration allows water to be transported from connected and well-watered ramets to ramets subjected to drought, thereby alleviating water stress in water-stressed ramets under heterogeneous water environments [15] , [35] [37] . Several studies have shown the effects of variable water availability on the morphology and gas exchange of clonal plants [3] , [15] , [36] , [38] [43] . However, no study has separated the effect of water stress on clonal plant from the effect of provision of support to a dependent ramet by a supporting one.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized as a large bedrock outcrop area with shallow soil, a discontinuous distribution, and complex and diverse micro-landforms. Previous studies have demonstrated a high diversity of microhabitats in karst regions [2], with diverse microclimatic characteristics in different microhabitats [3], and high spatial heterogeneity of soil nutrients, owing to uneven nutrient distribution and mobility [4,5], and of moisture [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Plants with high iWUE are better able to adapt to nutrient-and water-limited environments . Due to the greater hydraulic erosion and complex underground drainage network (Nie et al, 2014;Chen et al, 2015), karst soils cannot retain enough nutrients and water for plant growth even though precipitation is high (1000-2000 mm) (Liu et al, 2011;Fu et al, 2012;Chen et al, 2015). An understanding of the impact of CO 2 diffusion and the maximum carboxylase activity of Rubisco (V cmax ) on A and iWUE in karst plants can provide insight into the physiological strategies of water-carbon regulation of plants used in adaptation to karst environments at the leaf scale.…”
Section: Introductionmentioning
confidence: 99%